In Vitro Activity of Tebipenem (SPR859) against Penicillin-Binding Proteins of Gram-Negative and Gram-Positive Bacteria - Lacasse, Evelyne (Antimicrob Agents Chemother, 2019)
Tebipenem (SPR859) is the microbiologically active form of SPR994 (tebipenem-pivoxil), an orally available carbapenem with activity against extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae. Measurement of the relative binding of SPR859 to the bacterial cell targets revealed that it is a potent inhibitor of multiple penicillin-binding proteins (PBPs) but primarily a Gram-negative PBP 2 inhibitor, similar to other compounds in this class. These data support further clinical development of SPR994.